Chiral amplification in a cyanobiphenyl nematic liquid crystal doped with helicene-like derivatives - Ferrarini, Alberta; Pieraccini, Silvia; Masiero, Stefano; Spada, Gian Piero (Beilstein Journal of Organic Chemistry, 2009)
The addition of a chiral non-racemic dopant to a nematic liquid crystal (LC) has the effect of transferring the molecular chirality to the phase organization and a chiral nematic phase is formed. This molecular chirality amplification in the LC provides a unique possibility for investigating the relationship between molecular structure, intermolecular interactions, and mesoscale organization. It is known that axially chiral or helical-shaped molecules with reduced conformational disorder are good candidates for high helical twisting power derivatives. In particular, biaryl derivatives are known to be efficient chiral inducers in biaryl nematic mesophases. In this paper, we focus on a new series of helicene-like molecules of known absolute configuration. We have integrated cholesteric pitch measurements with geometry optimization by DFT calculations and analysis of the twisting ability by the Surface Chirality model to shed light on the structural features responsible for the analogies and differences exhibited by these derivatives. The investigation of these dopants with well-defined geometry, by virtue of the low conformational freedom, and the substituents variously distributed around the core, allows us to extend our knowledge of the molecular origin of the chirality amplification in liquid crystals and to confirm the simple relationship “molecular P-helicity” → “cholesteric P-handedness” for helical-shaped helicene-like derivatives.
Keywords: chirality; cholesteric; helical twisting power; helicene; nematic liquid crystal; Surface Chirality model